Polyelectrolytes in dilute solution: viscometric access to coil dimensions and salt effects - Suresha, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (RSC Advances, 2015)
Copolymers of acrylamide (AM) and diallyldimethylammonium chloride (DADMAC), differing in molar masses M (52.3 to 227 kDa) and degrees of charging y (0.2 to 0.6), were studied with respect to their viscometric behavior in dilute aqueous solutions containing variable amounts of NaCl. Complementary measurements were performed on a Brookhaven 90 plus particle size analyzer. M dominates the intrinsic viscosities [eta]. For the viscometric interaction parameters B this is only true for large concentrations of extra salt. [eta] and B as a function of solvent salinity follow Boltzmann laws. Coil dimensions, determined either via dynamic light scattering or viscometry, agree well. For low salt contents of the solvent the radii decrease with rising polymer concentration, whereas they increase for high salt concentrations; at a characteristic salinity of the solvent they become independent. Zeta potentials grow from +20 to +40 mV as y goes up.

Studies on use of sodium poly acrylate (SPA) for low salt animal skinpreservation - Sandhya, K. V.; Brindha, Velappan; Abinandan, Sudharsanam; Vedaraman, N.; John, Sundar V.; Suresha, P. R.; Badiger, Manohar; Chinnaraj, Velappan kandukalpatti; Muralidharan, C. (IULTCS CONGRESS 2017, 2017)
In this study, commercial sodium poly acrylate (SPA) is used along with sodium chloride for low salt skin preservation. SPA is a super-absorbent polymer which can absorb water many times of its own weight.

Flocculation of kaolin from aqueous suspension using low dosages of acrylamide-based cationic flocculants - Suresha, P. R.; Badiger, Manohar V. (Journal of Applied Polymer Science, 2019)
Flocculation of kaolin from aqueous streams has become very important in view of its wide range of applications. In this work, cationic flocculants based on copolymers of acrylamide (AM) and 3-acrylamidopropyltrimethylammonium chloride (APTMAC) were synthesized with two different mole ratios of monomers, 80 mol % of AM (CP-8020) and 40 mol % of AM (CP-4060). The chemical structures of copolymers were confirmed by H-1 and carbon-13 nuclear magnetic resonance (C-13 NMR) spectroscopy. The molecular weight (MW) and zeta potential of the copolymers were determined. High MW was obtained for copolymer with high content of AM (CP-8020) and high zeta potential was observed for copolymer with high content of APTMAC (CP-4060). Flocculation of kaolin suspension was performed using both CP-8020 and CP-4060 and the flocculation was correlated to the zeta potential and MW of the copolymers. The optimum dosages of flocculants were determined. The mechanism of flocculation was discussed in terms of charge neutralization and bridging. The flocs of kaolin were characterized in terms of moisture content and size. To the best of our knowledge, this copolymer system was used for the first time for kaolin flocculation and found out to be efficient. (c) 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47286.
Keywords: copolymers; hydrophilic polymers; polyelectrolytes

Drug-drug cocrystals of anticancer drugs erlotinib-furosemide and gefitinib-mefenamic acid for alternative multi-drug treatment - George, Christy P.; Thorat, Shridhar H.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (Crystengcomm, 2020)
Drug-drug cocrystals of anticancer drugs erlotinib and gefitinib with furosemide and mefenamic acid, respectively, have been synthesized. The 1:1 erlotinib-furosemide cocrystal crystallizes in the monoclinic centrosymmetric P2(1)/n space group containing one molecule of each component in the asymmetric unit. In contrast the 1:1 gefitinib-mefenamic acid cocrystal hydrate belongs to the monoclinic centrosymmetric P2(1)/c space group comprising one molecule of both drugs along with one water molecule in the asymmetric unit. The solubility and dissolution rate study revealed higher solubility for BCS class II drugs, furosemide, and mefenamic acid, while the solubility and dissolution rate of erlotinib showed a significant reduction in the cocrystal salt. Conversely, the solubility of gefitinib didn't reveal a substantial decrease; however, the dissolution rate has been reduced in the cocrystal hydrate. Further, an attempt has been made to correlate the crystal structures of the erlotinib-furosemide and gefitinib-mefenamic acid cocrystals with their solubilities and dissolution rate.

Design and synthesis of a new topical agent for halting blood loss rapidly: a multimodal chitosan-gelatin xerogel composite loaded with silica nanoparticles and calcium - Patil, Gokul; Torris, Arun; Suresha, P. R.; Jadhav, Sachin; Badiger, V. Manohar; Ghormade, Vandana (Colloids and Surfaces B-Biointerfaces, 2021)
Uncontrolled hemorrhage often causes death during traumatic injuries and halting exsanguination topically is a challenge. Here, an efficient multimodal topical hemostat was developed by (i) ionically crosslinking chitosan and gelatin with sodium tripolyphosphate for (ii) fabricating a robust, highly porous xerogel by lyophilization having 86.7 % porosity, by micro-CT and large pores similar to 30 mu m by SEM (iii) incorporating 0.5 mg synthesized silica nanoparticles (SiNPs, 120 nm size, -22 mV charge) and 2.5 mM calcium in xemgel composite that was confirmed by FTIR analysis with peaks at 3372, 986 and 788 cm(-1), respectively. XPS analysis displayed the presence of SiNPs (Si2p peak for silicon) and calcium (Ca2p1, Ca2p3 transition peaks) in the composite. Interestingly, in silico percolation simulation for composite revealed interlinked 800 mu m long-conduits predicting excellent absorption capacity and validated experimentally (640 % of composite dry weight). The composite achieved >16-fold improved blood clotting in vitro than commercial Celox and Gauze through multimodal interaction of its components with RBCs and platelets. The composite displayed good platelet activation and thrombin generation activities. It displayed high compressive strength (2.45 MPa) and withstood pressure during application. Moreover, xerogel composite showed high biocompatibility. In vivo application of xerogel composite to lethal femoral artery injury in rats achieved hemostasis (2.5 min) significantly faster than commercial Celox (3.3 min) and Gauze (4.6 min) and was easily removed from the wound. The gamma irradiated composite was stable till 1.5 yr. Therefore, the xerogel composite has potential for application as a rapid topical hemostatic agent.
Keywords: Hemostatic; Polymer; silica nanoparticles; Xerogel

Polymorphs and hydrates of the anticancer drug erlotinib: X-ray crystallography, phase transition and biopharmaceutical studies - Thorat, Shridhar H.; George, Christy P.; Shaligram, Parth S.; Suresha, P. R.; Gonnade, Rajesh G. (CrystEngComm, 2021)
Erlotinib, a non-small cell lung cancer BCS class II drug, was found to occur as two polymorphs and two hydrates depending on the crystallization conditions. The monohydrate (form III), which has been reported in patents and publications, is the preferred crystalline phase from solution crystallization. The other forms (polymorphs, forms I and II, and a trihydrate, form IV) are solvent and condition-specific. Form I was exclusively and reproducibly obtained from dried non-polar solvents (viz. toluene, benzene, and xylene) using a solution crystallization method under controlled conditions. In contrast, form II was obtained by the rotary evaporation technique under reduced pressure from polar solvents (viz. dichloromethane, ethyl acetate, acetone, and acetonitrile). Slow evaporation from polar and non-polar solvents under open conditions yielded form III crystals, whereas evaporation from acetone-acetonitrile-water mixtures yielded form IV crystals. DSC and variable temperature PXRD studies revealed form I to be the most stable phase while the other solid forms displayed thermally induced polymorphic transitions into form I crystals. Further, form I and form III are found to be stable over the 30-90% RH range. Further, form I displayed solution-mediated transformation into form III (monohydrate) when left to stand in the mother liquor for a longer duration (1-2 days). Similarly, the unstable form IV crystals transformed into the stable form III crystals within 1-2 h when exposed to an open atmosphere. Fast crystallization from polar solvents using the rotary evaporation technique enabled us to capture the metastable polymorph, form II. Early separation of form I from its mother liquor prevented its solution-mediated transformation into the monohydrate, form III. The water activity study revealed that form III is the most preferred solid phase in the presence of water. Dissolution rate measurements showed that the rate of form II is almost comparable to that of the marketed erlotinib hydrochloride. In contrast, for the other forms, the dissolution profiles showed a considerable decrease. Although the crystal structures of form I and form III have been published previously, this manuscript gives a comprehensive overview of the free base solid forms of erlotinib, the phase transitions amongst them and their biopharmaceutical properties.

Application of eco-friendly cationic celluloses for effective sludge dewatering - Menon, Snehal; Suresha, P. R.; Khairnar, Ajay; Kalyanraman, V. (Water Air and Soil Pollution, 2024)
The study presents the application of cationic celluloses in sludge dewatering. The source of cellulose used in this study were microcrystalline cellulose and alkaline-treated rice straw. The cationic celluloses were synthesized in a two-step reaction involving oxidation of cellulose with sodium periodate and followed by Schiff base reaction with Girard reagent T to introduce quaternary ammonium cations. The functional groups and chemical structure were confirmed by FTIR and NMR spectroscopy. The molecular weight and cationicity index of cationic cellulose were determined. Owing to their low molecular weight, the cationic celluloses functioned as coagulants and brought about charge neutralization through electric patches. The cationic celluloses were effective in promoting rapid sludge settling and improving the sludge filterability. The cationic celluloses are eco-friendly and non-toxic alternatives to acrylamide-based flocculants.
Keywords: biodegradable; Cationic cellulose; coagulation; Sludge dewatering; Wastewater treatment